Whole Blood Selective Aortic Arch Perfusion for Exsanguination Cardiac Arrest: Assessing Myocardial Tolerance to the Duration of Cardiac Arrest. Issue 6 (June 2022) - Madurska, Marta J.; Abdou, Hossam; Elansary, Noha N.; Edwards, Joseph; Patel, Neerav; Stonko, David P.; Richmond, Michael J.; Scalea, Thomas M.; Rasmussen, Todd E.; Morrison, Jonathan J.
ABSTRACT: Introduction: Selective aortic arch perfusion (SAAP) is an endovascular technique that consists of aortic occlusion with perfusion of the coronary and cerebral circulation. It been shown to facilitate return of spontaneous circulation (ROSC) after exanguination cardiac arrest (ECA), but it is not known how long arrest may last before the myocardium can no longer be durably recovered. The aim of this study is to assess the myocardial tolerance to exsanguination cardiac arrest before successful ROSC with SAAP. Methods: Male adult swine (n = 24) were anesthetized, instrumented, and hemorrhaged to arrest. Animals were randomized into three groups: 5, 10, and 15 min of cardiac arrest before resuscitation with SAAP. Following ROSC, animals were observed for 60 min in a critical care environment. Primary outcomes were ROSC, and survival at 1-h post-ROSC. Results: Shorter cardiac arrest time was associated with higher ROSC rate and better 1-h survival. ROSC was obtained for 100% (8/8) of the 5-min ECA group, 75% (6/8) of the 10-min group, 43% (3/7) of the 15-min group ( P  = 0.04). One-hour post-ROSC survival was 75%, 50%, and 14% in 5-, 10-, and 15-min groups, respectively ( P  = 0.02). One-hour survivors in the 5-min group required less norepinephrine (1.31 mg ± 0.83 mg) compared with 10-SAAP (0.76 mg ± 0.24 mg), P  = 0.008. Conclusion: Whole blood SAAP can accomplish ROSC at high rates even after 10 min of unsupported cardiac arrest secondary to hemorrhage, with some viability beyond to 15 min. This is promising as a tool for ECA, but requires additional optimization and clinical trials. Animal Use Protocol, IACUC: 0919015.